(untitled) (Ibrahim Cardiac Medical Journal, 2021)
Background & objective: Each year millions of Muslims embark on a religious pilgrimage called the “Hajj” to Mecca in Saudi Arabia. The mass migration during the Hajj is unparalleled in scale, and pilgrims face numerous health hazards. Performing the tasks of pilgrimage is stressful and laborious and as such requires immense mental and physical fitness on the part of the pilgrims. But a substantial proportion of the pilgrims lack it. Besides, the hot and dry environment and untold overcrowding predispose them to the risk of many communicable diseases. The present study, was therefore, intended to find the pattern of diseases among Bangladeshi Hajj pilgrims at Mecca, Saudi Arabia. Methods: This descriptive cross-sectional study was carried out on Bangladeshi Hazz pilgrims in Mecca Saudi Arabia over a period of 1 month from mid-September to mid-October, 2015. A total of 710 pilgrims (18 or > 18 years) attending at Bangladeshi Hazz Medical Center (BHMC) in Mecca, Saudi Arabia during the period were consecutively included in the study after having voluntary verbal consent obtained from them. Diseases were diagnosed mainly on the basis of clinical signs and symptoms with provision of only random and fasting blood sugar estimation and ECG. The diagnosed diseases were grouped into major and minor problems or conditions and were treated as out-patient basis. Result: In the present study upper middle-aged (50 – 60 years) and elderly (≥ 60 years) pilgrims together formed nearly 73% of the patients with mean age of the patients being 56 years. Males were a bit higher than the females with male-female ratio being roughly 11:9. The study demonstrated that the commonest cause of out-patient visit was respiratory illness (41.2%) followed by diabetes (17.2%), peptic ulcer disease (PUD) (11.7%) and cardiovascular diseases (10.7%)(which included hypertension, new onset ischemia or exacerbation of preexisting ischemic heart diseases). A few (3.2%) of the patients presented with diarrhoeal diseases (loose motion or dysentery). Other minor ailments were allergy or dermatitis, insomnia, paronychia, anxiety, UTI, hemorrhoids, epistaxis, glossitis, oral ulcer, earache, conjunctivitis, worm infestation, spot bleeding etc., accounting for 4.8% of the patients. Conclusion: The study concluded that respiratory illness is the most common health problems among pilgrims visiting to Mecca, Saudi Arabia followed by diabetes, PUD and cardio-vascular diseases. The pilgrims should be educated in their home country before starting for pilgrimage as how to maintain their health in their new and challenging environment and Bangladesh Hazz Mission in Mecca should ensure enough medical support to them. Ibrahim Card Med J 2020; 10 (1&2): 96-101